2019
DOI: 10.1111/agec.12556
|View full text |Cite
|
Sign up to set email alerts
|

Effects of redistributing policy support on farmers’ technical efficiency

Abstract: The objective of this article is twofold: first, investigating the relationship between technical efficiency and decoupled direct payments of a sample of Italian farms prior to the application of the 2014–2020 Common Agricultural Policy reform; second, evaluating possible implications of alternative scenarios about distribution of direct payments on technical efficiency. To these aims, a stochastic frontier analysis is adopted. Results indicate that direct payments produce significant effects on technical effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…The diverse impacts are also confirmed in studies by Bonfiglio [40], who found that the effect of subsidies on the farms' technical efficiency can differ in terms of the function of factors, including their type of farming. Despite these highly interesting findings, the authors point to certain imperfections in their studies.…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…The diverse impacts are also confirmed in studies by Bonfiglio [40], who found that the effect of subsidies on the farms' technical efficiency can differ in terms of the function of factors, including their type of farming. Despite these highly interesting findings, the authors point to certain imperfections in their studies.…”
Section: Introductionsupporting
confidence: 53%
“…First of all, there are some reservations as to the analysis period, which was only one year. The authors believe that a longer time perspective could yield more reliable findings [40]. Therefore, unlike their research project, the analysis presented in this paper covers a broader time frame (12 years) and a larger territory (eight countries).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…There are a few empirical studies that have examined this subject. Using Italian farms as a case study, Bonfiglio et al [47] examined the effects of decoupled payments on technical efficiency. The study found that direct payments still exert a significant impact on farms' ability in converting inputs to outputs.…”
Section: Previous Studiesmentioning
confidence: 99%
“…The development of the processes of Russia's integration into the global world economy justifies the need to establish an effective mechanism for state regulation of both agricultural production and foreign economic activity in the agricultural sector at the national and regional level, based on the innovative component and aimed, on the one hand, to realize Russian national interests and food security of the country, and on the other hand, for the quick and effective integration of Russia into the global agricultural and food market [8].Whether Russia will actively export surplus of the agricultural products or, on the contrary, import products that it can not or does not want to produce domestically; whether it will be an active participant in the market of finished food products, semi-finished products, raw materials or means of production,it will not be able to do without competition and interaction with foreign partners and rivals [3,9].And the effectiveness of such interaction, in turn, requires recognition of the need for state regulation and support of the agroindustrial complex, study of the foreign experience of such support and selection of the most effective and suitable examples for Russian practice, their reasonable adaptation and careful perception, as well as the monitoring the effectiveness of the application and adjustment of the measures as needed.…”
mentioning
confidence: 99%